1992
DOI: 10.1111/j.1600-0404.1992.tb05108.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an altered dopamine-hydroxylase activity in migraine and tension-type headache

Abstract: Sympathetic dysfunction is often present in migraine. It has been suggested that serum dopamine-beta-hydroxylase (D beta H) can be taken as an index of peripheral sympathetic activity. We studied the serum D beta H activity in migraine with and without aura and in tension-type headache patients compared with healthy control subjects. The serum D beta H activity was significantly lower in migraine and tension-type headache patients than in the control group. No significant difference was observed among the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 32 publications
(14 reference statements)
0
23
0
Order By: Relevance
“…Neurol Sci (2015) 36 (Suppl 1):S17-S22 platelet DA levels are elevated in MwoA patients [31,39]; a polymorphism of the gene that code for DbH may be the cause of a reduction of this enzyme activity [40] and of the high levels of DA [41,42] since DbH transforms DA in NE.…”
Section: Glutamate and Auramentioning
confidence: 98%
“…Neurol Sci (2015) 36 (Suppl 1):S17-S22 platelet DA levels are elevated in MwoA patients [31,39]; a polymorphism of the gene that code for DbH may be the cause of a reduction of this enzyme activity [40] and of the high levels of DA [41,42] since DbH transforms DA in NE.…”
Section: Glutamate and Auramentioning
confidence: 98%
“…More recently, in a separate study, the DBH insertion/deletion has been associated with migraine with aura [Fernandez et al, 2006]. As both genetic markers of DBH have been reported to be associated with differences in plasma and CSF levels of DBH [Cubells et al, 1998;Zabetian et al, 2003], and significant differences in serum DBH have been observed in migraine patients compared with control subjects [Gallai et al, 1992;Gotoh et al, 1976] and during a migraine attack [Anthony, 1981], DBH may play an important role in migraine and may prove to be a future target for specific migraine therapeutics. Anti-dopaminergic agents such as metoclopramide have been reported as effective treatments for migraine [Colman et al, 2004].…”
Section: Neurotransmitter-related Genesmentioning
confidence: 96%
“…Actually, in some migraineurs, the level of plasma NE levels has been measured as being significantly lower in patients compared to controls [9], indicating a sympathetic dysfunction. In addition, significant differences of serum dopamine beta-hydroxylase activity (DBH) have been observed in migraine (MO and MA) patients compared with healthy control subjects [10].…”
Section: Introductionmentioning
confidence: 99%